Aquablation therapy for symptomatic benign prostatic hyperplasia: a single‐centre experience in 47 patients. (4th February 2018) - Desai, Mihir M.; Singh, Abhishek; Abhishek, Shashank; Laddha, Abhishek; Pandya, Harshad; Ashrafi, Akbar N.; Ganpule, Arvind P.; Roehrborn, Claus G.; Thomas, Andrew J.; Desai, Mahesh; Sabnis, Ravindra B.
Abstract : Objective: To report procedure process improvements and confirm the preserved safety and short‐term effectiveness of a second‐generation Aquablation device for the treatment of lower urinary tract symptoms (LUTS) attributable to benign prostatic hyperplasia (BPH) in 47 consecutive patients at a single institution. Patients and Methods: Aquablation was performed in 47 patients with symptomatic BPH at a single institution. Baseline, peri‐operative and 3‐month urinary function data were collected. Results: The mean (range) patient age was 66 (50–79) years, and transrectal ultrasonography‐measured prostate volume was 48 (20–118) mL. A median lobe was present in 25 patients (53%) and eight patients had catheter‐dependent urinary retention. The mean (range) total procedure time was 35 (13–128) min and the tissue resection time was 4 (1–10) min. Five Clavien–Dindo grade I/II and five Clavien–Dindo grade III complications were recorded in eight patients. The mean (range) hospital stay was 3.1 (1–8) days and the mean (range) duration of urethral catheterization was 1.9 (1–11) days. The mean International Prostate Symptom Score (IPSS) decreased from 24.4 at baseline to 5 at 3 months; IPSS quality‐of‐life score decreased from 4.5 to 0.3 points; peak urinary flow rate increased from 7.1 to 16.5 mL/s and post‐void residual urine volume decreased from 119 to 43 mL (all P  <   0.01). Conclusions: This study confirmed procedure process improvements resulting from system enhancements, with preservation of safety and effectiveness during use of a second‐generation device for the treatment of LUTS attibutable to BPH in the largest single‐institution study conducted to date.